Mosaic structure of the DNA molecules of the human chromosomes 21 and 22 - Häring, D; Kypr, J (Molecular biology reports, 2001)
We calculated nucleotide distribution curves along the DNA molecules of the human chromosomes 21 and 22, their correlations in more than 10,000 equidistant positions, and subjected the correlations to cluster analysis. The cluster analysis demonstrated that both DNA molecules were composed of two types of segments exhibiting qualitatively different correlations. The segments differed most in the correlation of the distribution curves of cytosine and guanine, which was very high in type I segments but weak in type II segments. The type I and II segments also significantly differed in the correlations of the distribution curves of adenine with thymine. In addition, adenine strongly anticorrelated with cytosine but this anticorrelation was uniform along both chromosomes and, therefore, it did not contribute to the distinction of the two types of segments. The segments were up to 100 kbp long but they had nothing in common with isochores. Building blocks of the mosaic structure of the DNA molecules of the human chromosomes 21 and 22 are very similar but different in several interesting aspects from those of E. coli.
Keywords: konformace nukleové kyseliny; Humans; lidské chromozomy, pár 22; Nucleic Acid Conformation; DNA bakterií; DNA, Bacterial; lidé; Repetitive Sequences, Nucleic Acid; lidské chromozomy, pár 21; repetitivní sekvence nukleových kyselin; DNA; Escherichia coli; Chromosomes, Human, Pair 22; Chromosomes, Human, Pair 21